Understanding Cyber Crime Behavior on E-Commerce Application Users - Batmetan, Johan Reimon; Watung, Hensy; Nayoan, Leyri; Untu, Avandi E. (JR Education, 2022)
E-Commerce technology is a business mechanism that works electronically by focusing on online business transactions and has the opportunity to build more human and personalized relationships with customers without depending on space and time. The purpose of this study was to determine to what extent, the influence of Cyber ​​Crime behavior of users of e-commerce applications affects the level of trust of the users of E-Commerce transaction services. The data used in this study are primary data. The data analysis method used is quantified using a Likert scale. The population in this study was 30 respondents as the research sample, using the Google form. The results, based on the analysis showed that e-commerce users bear a lot of risks is added to the level of trust of E-Commerce users, making Cybercrime behavior is still very difficult to anticipate by users of E-Commerce transaction services, has a negative and significant effect. The results of this study conclude that the behavior of users in e-commerce is still low with the level of trust is not good and they are still worried about the risks of cybercrime they face